2015
DOI: 10.1111/anae.13040
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the McGrath®Series 5 videolaryngoscope and Macintosh laryngoscope for double-lumen tracheal tube placement in patients with a good glottic view at direct laryngoscopy

Abstract: SummaryWe compared the 3) s, p < 0.05) and a higher incidence of double-lumen tube malposition (6 (12.5%) vs 0, p < 0.05). However, in 18 non-randomised patients with Cormack and Lehane grade ≥ 2b on initial laryngoscopy using the Macintosh, the glottic view was improved on intubation with the McGrath videolaryngoscope, with a total success rate of double-lumen tube placement of 94.4% and mean (SD) intubation time of 50.0 (18.6) s. We recommend that in patients with a low airway risk index score requiring intu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 31 publications
(39 reference statements)
1
40
1
Order By: Relevance
“…A previous study showed that the McGrath Series 5 increased the incidence of DLT malposition. [12] In the present study, we found there was no significant difference in the incidence of DLT malposition between the 2 groups (6 patients in the Airtraq group and 10 patients in the McGrath group). Actually, DLT malposition was not an issue when using a videolaryngoscope in DLT intubation because fibre-optic bronchoscopy was routinely used for checking the position of the DLT.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…A previous study showed that the McGrath Series 5 increased the incidence of DLT malposition. [12] In the present study, we found there was no significant difference in the incidence of DLT malposition between the 2 groups (6 patients in the Airtraq group and 10 patients in the McGrath group). Actually, DLT malposition was not an issue when using a videolaryngoscope in DLT intubation because fibre-optic bronchoscopy was routinely used for checking the position of the DLT.…”
Section: Discussioncontrasting
confidence: 48%
“…[3,4] Furthermore, videolarynoscopes are recommended in cases of unexpected and expected difficult airway management. [5,6] Recently, many different types of video devices have been reported for use in DLT intubation including the GlideScope, [711] McGrath Series 5, [12,13] Airtraq, [14,15] CEL-100, [16,17] Pentax Airway Scope, [18] videolaryngoscopes with MAC blade, [19] video stylet, [20,21] and VivaSight-DL. [22,23] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the article by Yao et al. comparing the McGrath ® Series 5 videolaryngoscope (Aircraft Medical Limited, Edinburgh, UK) with the Macintosh laryngoscope for double‐lumen tracheal tube placement. They recommend that in patients with a low airway risk index score requiring intubation with a double‐lumen tracheal tube, the classic Macintosh laryngoscope is used as the initial device and the McGrath videolaryngoscope is used only if the classic Macintosh laryngoscope provides a poor glottic view.…”
mentioning
confidence: 99%
“…We read Yao et al. 's article comparing the McGrath Series 5 videolaryngoscope and Macintosh laryngoscope for double‐lumen tracheal tube (DLT) placement with interest , and would like to invite the authors to reply to several comments.…”
mentioning
confidence: 99%